Respon Pertumbuhan Bibit Kelapa Sawit ( Elais Guineensis Jacq.) Varietas DxP Simalungun Terhadap Aplikasi PGPR dan Trichoderma sp. Di Pre Nursery - Madani, Mohammad Faris; Wardati, Irma (Agropross : National Conference Proceedings of Agriculture, 2023)
Nurseries are important and play a major role in the development of upstream to downstream industries in oil palm plantations. One of the supporting factors affecting the productivity of oil palm plantations is the use of superior seeds. So far, there are still many oil palm nurseries that pay little attention to the type of soil used. The use of organic matter can be used to improve soil quality in terms of physical, chemical and biological properties as a place for growing oil palm seeds. Organic materials can increase the number of bacteria in the soil so that their use is more effective than just providing inorganic fertilizers. The purpose of this study was to determine the effect of PGPR and Trichoderma sp. on the growth of oil palm seedlings in the pre nursery phase. The implementation of the research entitled “Growth Response of Oil Palm Seeds (Elais guineensis Jacq.) DxP Simalungun Variety to the Application of PGPR and Trichoderma sp. In Pre-Nursery.” It will be held from July to November 2022 at the Plant and Field Protection Laboratory, Department of Agricultural Production, at an altitude of 104 meters above sea level. This study used a non-factorial randomized block design (RBD) consisting of 4 treatments. As for each treatment, P0: without the application of PGPR and Trichoderma sp. P1 : application of PGPR (density 105 CFU) P2 : application of Trichoderma sp. (density 108 spores/ml) P3 : PGPR application (density 105CFU) + Trichoderma sp. (density 108 spores/ml). Observational data were analyzed using analysis of variance (ANOVA), then it was tested further with LSD (Lessest Significant Difference) 5%. The results of this study indicate that the application of PGPR + Trichoderma sp. significant effect on the parameters of plant height at 11 WAP, stem diameter at 5, 7, 11 WAP, root volume at 11 WAP and highly significant effect on the number of leaves parameter at 9 and 11 WAP. The best treatment was the application of PGPR (density 105 CFU) + Trichoderma sp. (density 108 spores/ml) (P3)